Undergraduate Pharmacy Students Perceptions About The Importance of Work Safety and Health Management in The Laboratory for Reducing The Risk of Work Accidents - Pertiwi, Adisty Puspa (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to understand students' perceptions of occupational health and safety (OHS) management in laboratories to reduce the risk of work accidents. Methods: This qualitative study employs a phenomenological approach. Participants were selected using purposive sampling based on criteria established by the researchers, and data were collected through in-depth interviews. Results: The findings indicate that students are aware of and understand the importance of OHS management in laboratories. Individual work accidents in the laboratory were primarily due to personal negligence, often resulting from carelessness and lack of focus. The use of standard or specialized personal protective equipment (PPE) is crucial in reducing the risk of work accidents in the laboratory, following the applicable Standard Operating Procedures (SOP). The condition of the laboratory itself is also significant in minimizing work accident risks, as good ventilation systems greatly influence safety. Proper air exchange processes and the influx of fresh air into the room must be adequately maintained. The better the air circulation, the healthier the laboratory environment will be. Conclusion: This study concludes that numerous factors, both individual and environmental, can cause work accidents in laboratories. Students perceive the use of PPE as a small but essential step in reducing laboratory accidents. The PPE used must be comfortable, non-intrusive to work, and provide effective protection against specific hazards.